Sensitivity assessment of air and refrigeration - Nupur Goyal; Mangey Ram; Sagar Banga (Kuwait Journal of Science)
In engineering sector, research on a system is influenced by understanding the relationship between its physical components. Since, air and refrigeration system depends on its four essential physical components, namely, compressor, condenser, expansion device and the evaporator, the researchers adopt an appropriate mathematical model of an air and refrigeration system for measuring the system’s performance. In this research work, the reliability measures of a repairable air and refrigeration system is investigated, by which reliability engineers or designers can determine how reliability can be improved using appropriate vicissitudes. The sensitivity analysis for several variations in reliability characteristics along with the modifications in precise values of their input parameters has been done. At last, some numerical examples and their graphical representation have also been taken to highlight the practical utility of the model. Through the overall study, it is concluded that the power supply in air and refrigeration system required extra care, it is the most sensitive part of air and refrigeration system’s performance with respect to its other components.